Inhibitory control in young adult women with fetal alcohol syndrome: Findings from a pilot functional magnetic resonance imaging study. - Rau, Johanna M. H.; Sundermann, Benedikt; Pfleiderer, Bettina; Dehghan‐Nayyeri, Mahboobeh; Garde, Stefan; Weglage, Josef; Feldmann, Reinhold (Alcohol, Clinical & Experimental Research, 2023)
Background: Executive dysfunction, especially impaired inhibitory control, is a common finding in individuals with fetal alcohol syndrome (FAS). Previous research has mostly focused on neural correlates of inhibitory deficits in children and adolescents. We investigated inhibitory functions and underlying cerebral activation patterns in young adult women with FAS. Methods: Task performance and functional magnetic resonance imaging (fMRI) data were acquired during a Go/NoGo (GNG) inhibition task in 19 young adult women with FAS and 19 healthy female control subjects. Whole‐brain activation and task performance analyses were supplemented by region of interest (ROI) analyses of fMRI data within a predefined cognitive control network (CCN). Results: Task performance did not differ significantly between groups on errors of commission, associated with inhibitory control. Similarly, overall activation within the preselected ROIs did not differ significantly between groups for the main inhibitory contrast NoGo > Go. However, whole‐brain analyses revealed activation differences in the FAS group when compared to controls under inhibitory conditions. This included hyperactivations in the left inferior frontal, superior temporal, and supramarginal gyri in the FAS group. Likewise, lateralization tendencies toward right‐hemispheric ROIs were weaker in FAS subjects. In contrast to comparable inhibitory performance, attention‐related errors of omission were significantly higher in the FAS group. Correspondingly, FAS subjects had lower activity in attention‐related temporal and parietal areas. Conclusions: The known alterations of inhibitory functions associated with prenatal alcohol exposure in children and adolescents were not seen in this adult sample. However, differential brain activity was observed, reflecting potential compensatory mechanisms. Secondary results suggest that there is impaired attentional control in young adult women with FAS.